MANAJEMEN MUTU PENDIDIKAN ISLAM - Asrita, Riswel (Hijri, 2022)
The purpose of this writing is to find out the quality management of Islamic education, because management is a process that must be carried out to achieve certain goals that require planning, thought, regulation and direction so that it can run well and requires the combination of all existing potentials effectively and efficiently. Quality is a high standard and cannot be surpassed. Usually referred to by the terms good, superior, beautiful, good, expensive, luxurious and so on. If related to the educational context, the concept of educational quality is elite, because only a few institutions can provide high quality educational experience to students. Therefore Islamic Education Quality Management is one way to improve quality that relies on the educational institution/school itself, applies a set of methods, based on the availability of quantitative and qualitative data, and empowers all members.Keywords: Islamic Education Quality Management